Numerical simulation of ice plugging process using multi-jacket method in nuclear power pipes - Zhang, Wei; Xu, Ke; Hu, Ming-Lei; Liang, Hui-Jie; Chen, Hao; Wang, Li-Qun; Feng, Yong-Qiang (Frontiers in Energy Research, 2024)
Ice plugs acts as isolate maintenance sections during pipeline repairs in nuclear power plants can effectively reduce maintenance costs, which is formed by the cooling of liquid nitrogen. The singlejacket freezing method takes a long time for the formation of ice plugs with a certain load-bearing capacity, increasing the liquid nitrogen consumption. In this study, a multiple-jacket method for the formation of ice plugs was proposed, and the numerical simulation using CFD (Computational Fluid Dynamics) was conducted. The effects of total jacket length and jacket number on freezing time and the consumption of liquid nitrogen were analyzed. Research indicated that the multiple-jacket method obtained a 11% 15% decrease in freezing time and a 18% 26% decrease in liquid nitrogen consumption than the single-jacket method. For the multiple-jacket method, the gap between the jackets presented a certain influence on the freezing time and liquid nitrogen consumption. As the gap between the jackets increases, there exist a small increase in the freezing time, but the liquid nitrogen consumption will be reduced by 2% to 5%.